Composition and Functionality of Lipid Emulsions in Parenteral Nutrition: Examining Evidence in Clinical Applications - Sadu Singh, Birinder Kaur; Narayanan, Sreelakshmi Sankara; Khor, Ban Hock; Sahathevan, Sharmela; Abdul Gafor, Abdul Halim; Fiaccadori, Enrico; Sundram, Kalyana; Karupaiah, Tilakavati (Frontiers in Pharmacology, 2020)
Lipid emulsions (LEs), an integral component in parenteral nutrition (PN) feeding, have shifted from the primary aim of delivering non-protein calories and essential fatty acids to defined therapeutic outcomes such as reducing inflammation, and improving metabolic and clinical outcomes. Use of LEs in PN for surgical and critically ill patients is particularly well established, and there is enough literature assigning therapeutic and adverse effects to specific LEs. This narrative review contrarily puts into perspective the fatty acid compositional (FAC) nature of LE formulations, and discusses clinical applications and outcomes according to the biological function and structural functionality of fatty acids and co-factors such as phytosterols, α-tocopherol, emulsifiers and vitamin K. In addition to soybean oil-based LEs, this review covers clinical studies using the alternate LEs that incorporates physical mixtures combining medium- and long-chain triglycerides or structured triglycerides or the unusual olive oil or fish oil. The Jaded score was applied to assess the quality of these studies, and we report outcomes categorized as per immuno-inflammatory, nutritional, clinical, and cellular level FAC changes. It appears that the FAC nature of LEs is the primary determinant of desired clinical outcomes, and we conclude that one type of LE alone cannot be uniformly applied to patient care.